THE EFFECT OF E-SERVICE QUALITY AND E-TRUST ON CUSTOMER SATISFACTION THROUGH SHOPEE FOOD FEATURES AT MSMEs IN BANDUNG - Adhany Cantika Putri; Marheni Eka Saputri (SEAN Institute, 2023)
Shopee has the Shopee Food feature, this makes it interesting because Shopee is the first e-commerce to have online food delivery. So that Shopee does not need to compete with other e-commerce, but competes with Go Food and Grab Food. This is also supported by the results of the pre-survey which shows there are problems with the service from Shopee Food which can affect customer satisfaction. This study aims to determine how much influence E-Service Quality and E-Trust have on Customer Satisfaction through the Shopee Food feature for MSMEs in Bandung. This study uses a quantitative method with the sampling technique used is non-probability sampling with purposive sampling. Data collection was through a questionnaire with a total sample of 97 respondents who are individuals or groups who use e-commerce Shopee Food to buy MSME products in the Bandung area. The data is then processed using the SPSS 25 for Windows application. The results of this study indicate that the variables e-service quality (X1) and e-trust (X2) have a positive and significant influence on customer satisfaction variables through the shopee food feature for MSMEs in Bandung (Y).